Poor Glycemic Control and Its Contributing Factors Among Type 2 Diabetes Patients at Adama Hospital Medical College in East Ethiopia - Yosef T (Diabetes, Metabolic Syndrome and Obesity : Targets and Therapy, 2021)
Tewodros Yosef,1 Dejen Nureye,2 Eyob Tekalign3 1Department of Epidemiology and Biostatistics, School of Public Health, College of Medicine and Health Sciences, Mizan-Tepi University, Mizan Teferi, Ethiopia; 2Department of Pharmacology and Toxicology, School of Pharmacy, College of Medicine and Health Sciences, Mizan-Tepi University, Mizan Teferi, Ethiopia; 3Department of Medical Laboratory Science, College of Medicine and Health Sciences, Mizan-Tepi University, Mizan Teferi, EthiopiaCorrespondence: Tewodros YosefDepartment of Epidemiology and Biostatistics, School of Public Health, College of Medicine and Health Sciences, Mizan-Tepi University, P.O.Box: 260, Mizan Teferi, EthiopiaEmail tewodrosyosef47@mtu.edu.etBackground: Poor glycemic control is a major public health issue among patients with type 2 diabetes mellitus and a significant risk factor for the progression of diabetic complications. This study aimed to assess the magnitude and contributing factors of poor glycemic control among type 2 diabetes patients on follow-up at Adama Hospital Medical College (AHMC) in East Ethiopia.Methods: A cross-sectional study was conducted among 245 type 2 diabetes patients on follow-up at AHMC from March 1 to 30, 2020. All type 2 diabetes patients on follow-up at AHMC and fulfilling the inclusion criteria were included in the study. The data were collected through face-to-face interviews using structured questionnaires and reviewing the patient chart. The data were entered and analyzed using SPSS version 21. The level of significance was declared at a p-value of < 0.05.Results: Of the 245 type 2 diabetes patients included in the study, 157 (64.1%) had poor glycemic control. The factors associated with poor glycemic control were being male (AOR = 2.28, 95% CI [1.24– 4.21]), not attending formal education (AOR = 3.12, 95% CI [1.53– 6.35]), monthly income of < 136 USD (AOR = 2.14, 95% CI [1.17– 3.91]), overweight (AOR = 2.60, 95% CI [1.32– 5.10]) and obesity (AOR = 3.44, 95% CI [1.44– 8.21]), and chewing khat (AOR = 2.77, 95% CI [1.04– 7.33]).Conclusion: The proportion of poor glycemic control among type 2 diabetes patients at AHMC was remarkably high. Therefore, more effort should be taken to strengthening and disseminating health education programs for diabetes patients at each follow-up visit on the importance of achieving optimal body weight, avoiding khat chewing, and maintaining regular physical exercise to prevent and mitigate the complications resulting from poor glycemic control.Keywords: type 2 diabetes, glycemic control, AHMC, Ethiopia